3D geometry reconstruction from orthographic views: A method based on 3D image processing and data fitting - Governi, Lapo; Furferi, Rocco; Palai, Matteo; Volpe, Yary (Computers in industry, 2013)
[Display omitted] ► Despite a considerable interest of industrial and academic researchers, the automatic “translation” of a 2D hand drawing into a 3D computer model is still a challenging problem. ► This work presents a method based on 3D imaging which leads to the generation of a network of 3D spline curves and a set of surface patches, representing the surface model of the object to be reconstructed. ► Results obtained on a number of case studies demonstrate the effectiveness of the approach in automatizing the “translation” process, though some limitations still exist. Industrial esthetic designers typically produce hand-drawn sketches in the form of orthographic projections. A subsequent translation from 2D-drawings to 3D-models is usually necessary. This involves a considerably time consuming process, so that some automation is advisable. Common approaches to this “reconstruction problem” start directly from “exact” 2D vector representations or try to vectorize 2D raster images prior to the reconstruction phase. These approaches, however, typically fail to deal with free form geometries like the ones commonly found in esthetic industrial design. This work presents a new methodology suitable for free form geometries, comprising the generation and processing of a 3D voxel image obtained from a hand drawing, the creation of a set of 3D curves fitting the voxel image and the automatic generation of surface patches on the resulting curve network. Several case studies are also presented in order to emphasize and discuss strengths and weaknesses of the proposed method.